Social Entrepreneurial Orientation Impact On Social Entrepreneurial Intention Mediated Social Entrepreneurial Attitudes - Gilbert Fortino Orlando; Sabrina Sihombing (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2022)
Social inequality, poverty, and unemployment have now become serious problems experienced by the Indonesian state. The role of social entrepreneurs here is very important to be able to solve the problems of social inequality, poverty, and unemployment that occur in Indonesia. This study looks at how the dimensions or components of social entrepreneurial orientation (social vision, social proactiveness, innovation, and risk-taking motives) can influence or encourage a person's social entrepreneurial attitudes and intentions. This study uses a quantitative approach and a data collection strategy with an electronic questionnaire, using a non-probability sampling strategy, namely purposive sampling. The number of samples in this study were 185 respondents. The data that has been obtained was then analyzed using the CB-Structural Equation Model with the SPSS AMOS version 26 analysis tool. This study found that there were 5 supported hypotheses and 4 unsupported hypotheses. This research also provides theoretical implications, managerial implications, and suggestions for further research.